Pengelolaan Sistem Informasi Manajemen Rumah Sakit (SIMRS) di RSUD Labuang Baji Makassar - Mafarudin, Mafarudin; Amelia AP, Andi Reski; Haeruddin, Haeruddin; Mahmud , Amir (Mandalika Journal of Medical and Health Studies, 2024)
Information systems are systems that provide information for decision-making processes at every level within an organization. A hospital information system (HIS) integrates the collection, processing, reporting, and use of information needed to improve the efficiency and effectiveness of health services through better management at various levels of health services. Meanwhile, a hospital management information system (HMIS) is a specific information system designed to assist in the management and planning of health programs. This type of research is descriptive qualitative, describing or providing a subjective depiction of a situation, using semi-structured interview methods, which are a type of in-depth interview recorded using a tape recorder, and allowing more flexibility compared to structured interviews. The results of the study show that in the management of HMIS at RSUD Labuang Baji Makassar, staff in registration, medical records, doctor scheduling, inventory of medicines and medical equipment, as well as finance and billing, have not received formal training but have had initial socialization before using or operating the HMIS. The management supports its implementation, including the management of HMIS and the quality of the system from a technological perspective, ensuring data security with staff having usernames and passwords for accessing the HMIS server. For the hospital, it is important for hospital management to pay special attention to the management of HMIS to meet IT program needs and to provide training in HMIS management for every service unit.